2008
DOI: 10.13181/mji.v17i1.297
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Exercise-Induced Bronchospasm by laboratory exercise challenge among Ragunan Sport School athletes

Abstract: AbstrakExercise-induced bronchospasm (EIB) sering dijumpai pada atlet remaja. Penelitian untuk mengetahui prevalensi EIB pada atlet remaja di Indonesia belum pernah dilakukan. Penelitian ini dilakukan untuk mengetahui prevalensi EIB pada atlet Sekolah Olahraga Ragunan dengan menggunakan tes latihan di laboratorium. Setiap atlet melakukan latihan sepeda statis (Monark, Swedia) hingga mencapai intensitas latihan minimal pada 90% laju jantung maksimal. "Force expiratory ventilation" (FEV) diperiksa dengan menggun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Ten studies involving 1773 participants (223 cases of EIB) investigated the prevalence of EIB in child and adolescent athletes. Five studies recruited male soccer players, and other five studies included athletes of different modalities. The pooled prevalence of EIB was 15% (95% CI: 9‐21%) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies involving 1773 participants (223 cases of EIB) investigated the prevalence of EIB in child and adolescent athletes. Five studies recruited male soccer players, and other five studies included athletes of different modalities. The pooled prevalence of EIB was 15% (95% CI: 9‐21%) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty‐three studies investigated the prevalence of EIB in general population of children and adolescents. Ten studies reported the prevalence of EIB in child and adolescent athletes, and 23 studies in children and adolescents with asthma.…”
Section: Resultsmentioning
confidence: 99%
“…A total of ten studies with 3129 adolescent athletes were included, and their ages ranged from seven to 20 years. Three studies were conducted in the USA [ 15 - 17 ], one in Greece [ 18 ], one in Tunisia [ 19 ], one in Poland [ 20 ], one in Japan [ 21 ], one in Germany [ 22 ], one in Iran [ 23 ], and one in Brazil [ 24 ]. Five studies were cross-sectional studies [ 15 , 16 , 19 , 21 , 23 ], three were cohort studies [ 18 , 22 , 24 ], one was a prospective study [ 20 ], and one was an observational study [ 17 ].…”
Section: Reviewmentioning
confidence: 99%